Kontradiksi dalam Hubungan Pasangan (Analisis Semiotika Ferdinand de Saussure pada Film Sore: Istri dari Masa Depan): Penelitian - Putri, Nurfia Devi Friesta; Iskandar, Farid (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The film Sore: Istri dari Masa Depan tells the story of a woman named Sore, the wife of a man named Jo, who travels back into Jo’s past with the intention of improving his life. This study seeks to analyze the contradictions in marital relationships as represented in the film through Ferdinand de Saussure’s semiotic analysis and Baxter and Montgomery’s relational dialectics theory. The research focuses on how Sore’s efforts to transform Jo into a “better” person create tensions with Jo’s desire to preserve his personal freedom. The novelty of this study lies in combining Saussure’s semiotic framework with relational dialectics theory, providing a more comprehensive understanding of relational dynamics as represented in film. The findings reveal that semiotic analysis uncovers signs and meanings in several key scenes, including the imposition of lifestyle changes, negotiations over smoking and alcohol consumption, and the eventual realization of acceptance within the relationship. Furthermore, the resolution of relational tensions is achieved through segmentation and integration strategies, which serve as the main approaches to managing contradictions via neutralization, reframing, and disqualification.